The Important Role of Adiponectin and Orexin-A, Two Key Proteins Improving Healthy Status: Focus on Physical Activity - Polito, Rita; Monda, Vincenzo; Nigro, Ersilia; Messina, Antonietta; Di Maio, Girolamo; Giuliano, Maria Teresa; Orrù, Stefania; Imperlini, Esther; Calcagno, Giuseppe; Mosca, Laura; Mollica, Maria Pina; Trinchese, Giovanna; et al. (Frontiers in Physiology, 2020)
Exercise represents the most important integrative therapy in metabolic, immunologic and chronic diseases; it represents a valid strategy in the non-pharmacological intervention of lifestyle linked diseases. A large body of evidence indicates physical exercise as an effective measure against chronic non-communicable diseases. The worldwide general evidence for health benefits are both for all ages and skill levels. In a dysregulated lifestyle such as in the obesity, there is an imbalance in the production of different cytokines. In particular, we focused on Adiponectin, an adipokine producted by adipose tissue, and on Orexin-A, a neuropeptide synthesized in the lateral hypothalamus. The production of both Adiponectin and Orexin-A increases following regular and structured physical activity and both these hormones have similar actions. Indeed, they improve energy and glucose metabolism, and also modulate energy expenditure and thermogenesis. In addition, a relevant biological role of Adiponectin and Orexin A has been recently highlighted in the immune system, where they function as immune-suppressor factors. The strong connection between these two cytokines and healthy status is mediated by physical activity and candidates these hormones as potential biomarkers of the beneficial effects induced by physical activity. For these reasons, this review aims to underly the interconnections among Adiponectin, Orexin-A, physical activity and healthy status. Furthermore, it is analyzed the involvement of Adiponectin and Orexin-A in physical activity as physiological factors improving healthy status through physical exercise.